We have to find the values of x that satisfy the equation (u+3)/8 = 5/( u-3)

(u+3)/8 = 5/( u-3)

multiply both sides by (u - 3)

=> (u +3 )(u - 3) = 5*8

=> u^2 - 3^2 = 40

=> u^2 - 9 = 40

=> u^2 = 40+9

=> u^2 = 49

=> u = -sqrt 49 and sqrt 49

=> u = -7 and 7

**Therefore u can be equal to 7 and -7.**

(u+ 3)/8 = 5/(u-3).

To solve the equation, we need to cross multiply.

==> (u+3)*(u-3) = 8*5

==> (u+3)(u-3) = 40.

Now we will expand the brackets.

==> u*u + 3*u + u*-3 + 3*-3 = 40

==> u^2 + 3u - 3u - 9 = 40

Now we will reduce similar terms.

==> u^2 - 9 = 40

Now we will add 9 to both sides.

==> u^2 = 40+9

==> u^2 = 49.

Now we will take the root of both sides.

==> u= +- 7.

Then, there are two possible values for u that satisfies the equation.

**==> u = { -7, 7}**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now